Sistem Informasi Akuntansi dan Kinerja Keuangan Usaha Kecil dan Menengah - Risma Nurhapsari; Kusna Djati Purnama (Jurnal Akuntan Publik, 2023)
This study seeks to determine the effect of Accounting Information System (AIS) on the financial performance of Small and Medium Enterprises (SMEs) with the aim of investigating the impact of recording systems, financial reporting systems, budget control systems, and cash management systems on financial performance. Entering and documenting daily business transactions manually has become impractical and from here organizations have realized the usefulness of adopting AIS to improve company performance. The study's findings provide valuable insights for SME owners, policymakers, and researchers interested in improving the financial performance of small businesses. adopt a descriptive research design and target 1640 SMEs This study used questionnaires as data collection instruments. Trials are conducted to ensure the validity and reliability of the tool. The Statistics Package for Social Sciences version 24 is used to analyze data using descriptive analysis and inferential statistics. The results of this study show that there is a strong significant relationship between the financial reporting system and the financial performance of SMEs. In addition, several ways are also provided to improve the effectiveness of AIS which has a significant impact on the financial performance of SMEs. From the results found, it is advisable to research further on the same research area. In addition, several recommendations are given to improve financial performance through effective AIS for SME owners and policy makers.